Konsep riba dalam fikih perbandingan dan relevansinya terhadap perkembangan ekonomi digital - Inayah, Inayah; Yasmin, Rina (Prodi Perbandingan Madzab Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2025)
This study examines the concept of riba (usury) from the comparative perspectives of the four major Islamic jurisprudential schools (Hanafi, Maliki, Shafi’i, and Hanbali) and its implications on contemporary digital economic systems. The research is motivated by the increasing prevalence of interest-based transactions in digital financial services such as online loans, digital banks, and e-wallets, raising critical legal questions within the framework of Islamic commercial law (fiqh muamalah). Using a qualitative method based on literature review, the study analyzes both classical and contemporary sources related to riba. The findings reveal that all schools unanimously prohibit riba, despite differences in categorization and application. In the context of digital economics, interest and additional gains without a basis in real transactions fall under prohibited riba. This analysis is reinforced by the maqāṣid al-sharī‘ah approach, which allows for contextual ijtihad to address challenges posed by digital finance while upholding justice and protection principles. The study concludes that reconstructing the law of riba in a contextual yet sharia-compliant manner is essential to maintain the relevance of Islamic law in modern economic systems.